REVITALISATION OF FEMALE GAMELAN’S PLAYERS IN SEBLANG OF BAKUNGAN A STUDY CASE - Agnes Serfozo; Titis Srimuda Pitana; Wakit Abdullah (Universitas Sebelas Maret, 2019)
The local agricultural spirit of Osing people of Banyuwangi district, East Java produced many of various rites. These function as mediation between human community and supranatural forces to influence the fertility of soils even to guarantee the welfare of the community. Seblang is the oldest among these traditions, still kept and implemented by the villagers of Bakungan as a part of yearly village purification ceremony. The entity of woman as spiritual being associated to fertility and to the food-giving Mother Earth (pertiwi)and rice field goddess (Mbok Srindani)is essential in the Seblang ritual. Woman is also the preserver of local wisdom about ecological equilibrium as the part of the traditional agricultural worldview. In the last two decades myths, beliefs and discourses of Seblang changed, in parallel with the social-, cultural- ecological changes of the regional development leaded by Banyuwangi`s post-reformation government. This changes modificate elements in the original implementation of this rite. One of these changes was the arbitrary exchange of the Seblang`s female gamelan’s players by male ones five years ago. This paper analyzes how the changing power structures of center and periferic caused the marginalisation of female gamelan’s players of Seblang, in a concrete way, howthe dominant patriarchal class ignored the importance of female entity in the Seblang rite through the act of banishing the female gamelan’s players. After five years of their banishment, in 2018 Bakungan women got the opportunity to join again as gamelan’s player in Seblang. Present paper examines how the awareness of community about cultural competency the female gamelan’s players changed positively after Bakungan women were able to articulate their need to participate as musicians in the Seblang rite. This new awareness presents the emerging self-image of Osing woman and forming a change in the earlier male-dominant perspective.